2017
DOI: 10.1007/s00430-017-0515-0
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study among Polish hunters: seroprevalence of hepatitis E and the analysis of factors contributing to HEV infections

Abstract: Hepatitis E virus (HEV) is known as zoonotic agent. The main reservoirs of HEV in Europe are pigs, wild boars, and deer. Hunting activity is considered to be a risk factor for HEV infection. We conducted a cross-sectional study among 1021 Polish hunters. To understand socio-demographic characteristics of this population and to gather information on potential exposures, all participants completed a questionnaire. Commercial immunoassays were employed to estimate seroprevalence anti-HEV. Samples with confirmed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…Moreover, faeces or bile of infected animals may more easily contaminate pork meat, equipment and utensils during homemade processing [ 35 ]. Lastly, like others [ 36 , 37 ], we found an association between hunting and anti-HEV IgG positivity, but it was not statistically significant (p = 0.056). If skinning and disembowelling of infected animals such as wild boars or deer without gloves, hunters may have direct contact with body fluids or faeces [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, faeces or bile of infected animals may more easily contaminate pork meat, equipment and utensils during homemade processing [ 35 ]. Lastly, like others [ 36 , 37 ], we found an association between hunting and anti-HEV IgG positivity, but it was not statistically significant (p = 0.056). If skinning and disembowelling of infected animals such as wild boars or deer without gloves, hunters may have direct contact with body fluids or faeces [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 67%
“…Schielke et al analyzed 126 German hunters and 21% were positive for anti-HEV IgG antibodies (95% CI: 13.0–28.0) [ 64 ]. Baumann-Popczyk et al showed that anti-HEV IgG results were identified in 22.2% (227/1021) of the studied Polish hunters [ 65 ]. Montagnaro et al published an estimated HEV seroprevalence among Italian hunters (Latium region, Central Italy) of 25.0% (5/20; 95% CI: 6.1–43.9) [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main pertinent route of human infection is the fecal – oral, through consumption of meat, liver, and offal originating from infected wild boars [ 34 , 35 ]. Direct contact with infected animals also seems to be important, as the presence of anti-HEV antibodies has been detected more often among hunters and forest workers [ 21 , 36 , 37 , 38 , 39 ]. The phylogenetic analysis of the ORF2 sequences of the detected Polish wild boar HEV strains showed their affiliation to the third virus genotype.…”
Section: Discussionmentioning
confidence: 99%